CONTEMPORARY AMERICAN SATIRICAL NOVEL (Conferencea, 2023)
In this article the problem of contemporary American satirical novel has been put forward. Comic genres in every national literature play a significant role as they reflect cultural and historical peculiarities of people. Thus, American literature is not an exclusion, American comic literature despite all of its merits has not yet been thoroughly investigated. Therefore, this article is an attempt to define the phenomenon and to generalize all the existing theories in the field of comic.